2019
DOI: 10.1016/j.biomaterials.2019.119361
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical meniscus construct with zone specific biochemical composition and structural organization

Abstract: A PCL/hydrogel construct that would mimic the structural organization, biochemistry and anatomy of meniscus was engineered. The compressive (380 ± 40 kPa) and tensile modulus (18.2 ± 0.9 MPa) of the PCL scaffolds were increased significantly when constructs were printed with a shifted design and circumferential strands mimicking the collagen organization in native tissue (p<0.05). Presence of circumferentially aligned PCL strands also led to elongation and alignment of the human fibrochondrocytes. Gene express… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 46 publications
(97 reference statements)
0
51
0
Order By: Relevance
“…While the mechanical properties of both gels are relatively low for applications in large tissue defects subjected to continuous mechanical loads, several reinforcing strategies based on the combination or coprinting with stiff thermoplastic support scaffolds have already been reported in the literature to address this common limitation for bioinks. [ 51 54 ] Further analysis into the gene expression over the 28 day culture period showed that both collagen type II and type I expression was upregulated in the GelMA and GelMA-Tyr hydrogels ( Figure 3D,E ). It was also observed that the collagen type II expression is significantly higher in the GelMA-Tyr samples (0.8-fold) after 28 days as compared to GelMA (0.3-fold).…”
Section: Resultsmentioning
confidence: 99%
“…While the mechanical properties of both gels are relatively low for applications in large tissue defects subjected to continuous mechanical loads, several reinforcing strategies based on the combination or coprinting with stiff thermoplastic support scaffolds have already been reported in the literature to address this common limitation for bioinks. [ 51 54 ] Further analysis into the gene expression over the 28 day culture period showed that both collagen type II and type I expression was upregulated in the GelMA and GelMA-Tyr hydrogels ( Figure 3D,E ). It was also observed that the collagen type II expression is significantly higher in the GelMA-Tyr samples (0.8-fold) after 28 days as compared to GelMA (0.3-fold).…”
Section: Resultsmentioning
confidence: 99%
“…Collagen II is mainly produced by chondrocytes, aggrecan is mainly distributed in the ECM, and SOX9 is the earliest markers for MSC differentiation into chondrocytes [ 44 ]. Collagen X is commonly associated with chondrocyte hypertrophy and is expressed in MSCs that undergo chondrogenesis after 21 days of culture [ 45 ]. Moreover, the PMA-gradient scaffold exhibited significantly higher expression levels of collagen II, collagen X and SOX9 in comparison to the other networks, and the expression of aggrecan was slightly lower than DL-PMA networks.…”
Section: Resultsmentioning
confidence: 99%
“…A mixture of agarose and GelMA hydrogel was found to induce aggrecan expression and produce a high ratio of collagen type II/collagen type I in human fibrochondrocyte-hydrogel constructs. Moreover, the construct consisting of the blended hydrogel combined with the PCL scaffold perfectly mimicked the natural meniscal interior region (Bahcecioglu et al, 2019). Hyaluronic acid (HA) is a natural hydrophilic GAG that is found in connective tissue, such as cartilage ECM, and is especially abundant in synovial fluid (Zamboni et al, 2018;Shah et al, 2019).…”
Section: Polysaccharidesmentioning
confidence: 99%
“…Thus, gelatin modified with GelMA has also been studied as a polymeric meniscal scaffold. A study showed that GelMA in the construct significantly enhanced the adhesion of chondrocytes and the secretion of type II collagen ( Bahcecioglu et al, 2019 , 2019a ).…”
Section: Polymers For Meniscal Tissue Engineering Applicationsmentioning
confidence: 99%
See 1 more Smart Citation